2019
DOI: 10.1002/asna.201913631
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric activity behavior of an eclipsing binary system KOI 68AB

Abstract: We present the results obtained from KOI 68AB's light variation, which exhibits a sinusoidal light variation due to the stellar spots. Two active regions longitudinally separated by about 180° between the latitudes of +70° and +110° were found. A total of 313 flares were determined, and flare parameters were calculated. The One Phase Exponential Association model was derived using these parameters. The energy saturation parameter Plateau value was found to be 1.219 ± 0.088 s, and its time scale parameter half‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…out-of-eclipse phases, for which synthetic light curves were needed. In the case of KIC 8669092, one of the remaining five systems, the light curve analysis was recently done by Kaya & Dal (2019). We used the synthetic curve they derived to obtain the variations seen at out-of-eclipse phases of this system.…”
Section: Light Curve Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…out-of-eclipse phases, for which synthetic light curves were needed. In the case of KIC 8669092, one of the remaining five systems, the light curve analysis was recently done by Kaya & Dal (2019). We used the synthetic curve they derived to obtain the variations seen at out-of-eclipse phases of this system.…”
Section: Light Curve Analysesmentioning
confidence: 99%
“…Shibayama et al (2013) detected four flares from the observation data of KIC 4357272, while Gao et al (2016) found 58 flares from the same data. Balona (2015), Gao et al (2016), and Kaya & Dal (2019), who analysed the light variations of KIC 8669092, known as KOI 68AB, stated that the target is a binary system with an active chromospheric component. Also, Kaya & Dal (2019) detected 313 flares exhibited by the active component of KOI 68AB during an observation period of approximately 4 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tutulma dışındaki sinüzoidal değişimleri ortaya çıkarmak için, 4 hedef sistemin ışık eğrisi analizi yapılmıştır. Kalan 6 sistemden biri olan KIC 08669092 için ışık eğrisi analizi, Kaya & Dal (2019) tarafından yapılmıştır. Bu sistemin tutulma dışındaki değişimlerini elde etmek için ışık eğrisi analizinden elde ettikleri kuramsal eğri kullanılmıştır.…”
Section: Işık Eğrisi Analiziunclassified
“…Finally, magnetically active stars tend to exhibit flares or superflares (sudden releases of magnetic energy) [49], often large and rapidly evolving starspots (cooler regions where convection is suppressed by strong magnetic fields) [50][51][52][53][54], as well as faculae and plages (unusually bright regions in the photosphere and chromosphere, respectively) [8,55]. Dark starspots and bright faculae are usually located in stellar photospheres, whereas plages tend to be associated with chromospheres [55].…”
Section: Introductionmentioning
confidence: 99%